1991
DOI: 10.1021/jf00011a028
|View full text |Cite
|
Sign up to set email alerts
|

Fumonisin contamination of commercial corn-based human foodstuffs

Abstract: Corn-based human foodstuffs from retail outlets in five countries were analyzed for fumonisin Bi (FBi) and fumonisin B2 (FB2). The highest mean concentrations occurred in two Egyptian samples (2380 ng/g FBi and 595 ng/g FB2). Only one of four Peruvian samples contained 660 ng/g FBi and 68 ng/g FB2, while only one of two Canadian samples contained a detectable level of FBi. The 16 cornmeal (CM) and 10 corn grits (CG) products from the United States contained mean concentrations of 1048 ng/g FBi and 298 ng/g … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
138
1
5

Year Published

1996
1996
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 288 publications
(155 citation statements)
references
References 29 publications
11
138
1
5
Order By: Relevance
“…Since their factory. discovery, various authors have shown that fumonisins cause Using a strain isolated in this laboratory from French several animal diseases, often implicating F. moniliforme, maize, we have shown that mycelial growth, as reflected by which is frequently found in the fungal flora on cereals, in ergosterol levels (Cahagnier 1984), and the biosynthesis of France and elsewhere (Norred 1993;Scott 1993). The most FB1, are greater at higher values (unity) of the water activity abundant and toxic is FB1, which has been shown to induce (a w ) of the substrate (Cahagnier et al 1995).…”
Section: Fumonisins Are Mycotoxins Produced By Fusarium Moni-mentioning
confidence: 57%
“…Since their factory. discovery, various authors have shown that fumonisins cause Using a strain isolated in this laboratory from French several animal diseases, often implicating F. moniliforme, maize, we have shown that mycelial growth, as reflected by which is frequently found in the fungal flora on cereals, in ergosterol levels (Cahagnier 1984), and the biosynthesis of France and elsewhere (Norred 1993;Scott 1993). The most FB1, are greater at higher values (unity) of the water activity abundant and toxic is FB1, which has been shown to induce (a w ) of the substrate (Cahagnier et al 1995).…”
Section: Fumonisins Are Mycotoxins Produced By Fusarium Moni-mentioning
confidence: 57%
“…There is no direct evidence of FB 1 carcinogenic effect in humans, but an increase of oesophageal cancer is observed in areas where maize, either contaminated by Fusarium or containing high levels of FB 1 , is used as the main staple 5,50 . Fumonisins, mainly FB 1 , have been detected in a large array of maize products in all areas of the world where analyses of such commodities have been conducted 4,6,7,16,17,25,40,45 .…”
Section: Introductionmentioning
confidence: 99%
“…[101][102][103][104][105][106][107][108][109]. Poultry feed investigated in china was contaminated with 1854.3mg/kg (37).…”
Section: Occurrence Of Fumonisinmentioning
confidence: 99%